2005
DOI: 10.5511/plantbiotechnology.22.33
|View full text |Cite
|
Sign up to set email alerts
|

Brassinolide as a modulator of the activities of cell wall loosening proteins

Abstract: Brassinolide (BR) is an essential plant hormone required for normal growth (Clouse and Sasse 1998;Li and Chory 1999;Sasse 2003). Mutations impairing in its biosynthesis or perception result in dwarfism (Schumaker and Chory 2000;Bishop 2003). Stem growth is accomplished by cell proliferation and cell expansion, and stem elongation is usually due to cell elongation. A key control part of the cell in its expansion is the cell wall. The kinetics of cell wall expansion (extension) under the steady state condition i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Specifically, the majority of the 29 DEGs of GO:0071554 (cell wall organization and biogenesis) term, such as expansin, β-1,4-endoglucanase, pectin lyase, and cellulose synthase genes, which contribute to cell elongation and enlargement 24 – 29 , were upregulated in the overexpressing lines (Table S 3 and Table 1 ). Auxin and brassinosteroid (BR) hormones play important roles in plant cell growth 30 33 . Consistent with this, KEGG pathway analysis retrieved the plant hormone signal transduction pathway (cit04075) containing 20 genes (FDR < 0.05) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the majority of the 29 DEGs of GO:0071554 (cell wall organization and biogenesis) term, such as expansin, β-1,4-endoglucanase, pectin lyase, and cellulose synthase genes, which contribute to cell elongation and enlargement 24 – 29 , were upregulated in the overexpressing lines (Table S 3 and Table 1 ). Auxin and brassinosteroid (BR) hormones play important roles in plant cell growth 30 33 . Consistent with this, KEGG pathway analysis retrieved the plant hormone signal transduction pathway (cit04075) containing 20 genes (FDR < 0.05) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The auxin-inducible genes SAUR (auxin-induced protein), GH3 (indole-3-acetic acid-amido synthetase), and IAA (auxin-responsive protein) play vital roles in regulating cell wall loosening 30 , 31 , 51 . In addition, brassinosteroids (BRs) are known to promote cell enlargement by increasing the activities of the BRU1 and TCH4 genes, that encode the xyloglucan endotransglycosylase proteins responsible for cell wall relaxation 32 , 33 . In this study, we observed that the spongy mesophyll cells of CsWRKY22 -overexpressing plants were enlarged compared with those of the WT control (Fig.…”
Section: Discussionmentioning
confidence: 99%